2007
DOI: 10.1146/annurev.neuro.30.051606.094256
|View full text |Cite
|
Sign up to set email alerts
|

Fundamental Components of Attention

Abstract: A mechanistic understanding of attention is necessary for the elucidation of the neurobiological basis of conscious experience. This chapter presents a framework for thinking about attention that facilitates the analysis of this cognitive process in terms of underlying neural mechanisms. Four processes are fundamental to attention: working memory, top-down sensitivity control, competitive selection, and automatic bottom-up filtering for salient stimuli. Each process makes a distinct and essential contribution … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
657
2
10

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 831 publications
(690 citation statements)
references
References 94 publications
21
657
2
10
Order By: Relevance
“…One hypothesis supported by several experimental results (reviewed in Boehnke and Munoz 2008;Knudsen 2007) is that neurons in the SC integrate "bottom-up" with "top-down" information to signal the most important stimulus at any particular time. It is suggested that task-related information about the stimulus is conveyed to the SC through cortical and basal ganglia connections (Boehnke and Munoz 2008).…”
Section: What Is the Relationship Between Ssa And Behavior?mentioning
confidence: 99%
“…One hypothesis supported by several experimental results (reviewed in Boehnke and Munoz 2008;Knudsen 2007) is that neurons in the SC integrate "bottom-up" with "top-down" information to signal the most important stimulus at any particular time. It is suggested that task-related information about the stimulus is conveyed to the SC through cortical and basal ganglia connections (Boehnke and Munoz 2008).…”
Section: What Is the Relationship Between Ssa And Behavior?mentioning
confidence: 99%
“…a top-down process, for example, when we search for a certain brand of pasta on the shelves in a supermarket). Early attention components are associated with more involuntary, less controlled mechanisms, whereas later attention components are thought to reflect the slower top-down mechanisms of voluntary or more controlled processing (28,29) . At least three different methodologies have been applied in previous studies to asses visual attentional biases for food: (1) measuring response latencies or the calculation of an interference effect during a foodStroop task; (2) assessment of response latencies during a spatial attention paradigm, such as the visual probe task, the exogenous cueing task or the visual search task; (3) recordings of eye-movements during an attention paradigm.…”
Section: Assessment Of Visual Attention For Food: Many Roads Leadmentioning
confidence: 99%
“…Indeed, our capacity to process information is severely limited (Allport, 1989;Broadbent, 1958;Carrasco, 2011), suggesting that the way in which we prioritise signals is a critical mechanism driving detailed perception and goaldriven action. Given this limited capacity, it is broadly held that signals compete in order to achieve detailed analysis (Desimone & Duncan, 1995;Knudsen, 2007;Rescorla & Wagner, 1972). Adding to the complexity of the problem, there are several sources of bias influencing the outcome of this competitive process, originating from the physical properties of the world (Itti & Koch, 2001;Wolfe & Horowitz, 2004), as well as a variety of internal states .…”
Section: You May Infringe the Author's Moral Rights If Youmentioning
confidence: 99%
“…Rather, it is widely argued that behaviour reflects the dynamic interplay between top-down and bottom-up control (Carrasco, 2011;Desimone & Duncan, 1995;Knudsen, 2007;Pashler, Johnston, & Ruthruff, 2001). Indeed, it is this interplay that forms the basis for the influential framework of attentional control put forward by Desimone and Duncan (1995), namely the biased competition theory of selective attention.…”
Section: Learning To Attend: Effects Of Predictiveness On Perception mentioning
confidence: 99%